Peran PKBM dalam Meningkatkan Pendidikan di Daerah Pinggiran Kota - Rahman, Abdul; Suhandi, Andi; Nurlaela, Novalia; Yoseptry, Ricky; Ratnawulan, Teti; Premeilani, Premeilani (STKIP PGRI SITUBONDO, 2024)
People in the suburbs have the same opportunities as city people. The emergence of the Community Learning Activity Center (PKBM) as a non-formal education institution that is proactive in responding to community learning needs. By empowering community potential, PKBM is expected to become an instrument that encourages educational progress. The aim of this research is to find out all the learning processes at PKBM Hidayah which include: Planning, Organizing, Implementing, Evaluation, supporting and inhibiting factors, and efforts to improve. The research method uses qualitative descriptive research because the author wants to thoroughly understand the role of PKBM in improving the quality of education in the suburbs. The results of this research are described as follows: 1. Planning can be seen from the major programs taken, namely reducing illiteracy and providing skills to students. 2. Organizing, seen from the division of tasks starting from the head of the foundation who appoints the person in charge of each program, followed by appointing assistant teachers in each program by synchronizing each activity to suit the needs of the community. 3. Implementation, as evidenced by the number of Package C graduates who got jobs in the Bojongsoang sub-district government, 4. Evaluation has been ongoing, as seen by the increase in the Bojongsoang sub-district community graduate index. 5. Supporting and inhibiting factors, obstacles related to expert professional teaching staff are still few, 6. Efforts are focused on two things, namely eradicating illiteracy and providing skills.